Leprosy's risk factors and distribution pattern in Yogyakarta - Efrizal Efrizal; Lutfan Lazuardi; Hardyanto Soebono (Berita Kedokteran Masyarakat (BKM), 2016)
Risk factors and distribution of leprosy in YogyakartaPurposeThe purpose of this paper was to identify risk factors and distribution pattern of leprosy in Yogyakarta. MethodsA case-control study was conducted involving 112 samples which consisted of 56 cases and 56 controls. ResultsThe study found three risk factors of leprosy: BCG vaccination, humidity and lighting. BCG vaccination was the most dominant risk factor of leprosy. The study also showed that the distribution pattern of leprosy in Yogyakarta was clustered. BCG vaccination was the most dominant risk factor for leprosy occurrence. Distribution of leprosy events were wide-spread and dispersed in the city of Yogyakarta, Sleman, Bantul and Kulon Progo, and only in Gunung Kidul Regency were clustered, and overall in Yogyakarta Special Region was clustered. The existence of cases of leprosy was largely distant with primary health care, away from roads and rivers as well as more dominant in settlements in mountainous areas.ConclusionActive case finding of leprosy by health workers, especially in clustered areas to decide the transmission of leprosy either from humans or the environment, with training of leprosy and counseling officers to remove leprosy-related stigma needs to be done. These efforts need to be coordinated between the Health Office and community health centers so that the number of cases in each region can be known.